ZnS-based quantum dots as photocatalysts for water purification. (October 2021) - Sharma, Kusum; Raizada, Pankaj; Hasija, Vasudha; Singh, Pardeep; Bajpai, Archana; Nguyen, Van-Huy; Rangabhashiyam, S.; Kumar, Pawan; Nadda, Ashok Kumar; Kim, Soo Young; Varma, Rajender S.; Le, Thi Thanh Nhi; et al.
Abstract: Solar-light-driven photocatalysis is an emerging, renewable and sustainable approach in environmental remediation to mitigate organic pollutants from waste water. Zinc sulfide quantum dots (ZnS QDs) have been utilized because of their larger surface area, low cost, abundant active sites, non-toxic nature, aqueous insolubility, and good thermal stability. Ascribing to the quantum confinement effect, the accumulation of the electrons inside the QDs leads to an increase in the light absorption range. Herein, the effect of various parameters, like pH and temperature variation are summarized that determines the size and varied morphologies of ZnS QDs including their synthesis via solvothermal, hydrothermal, coprecipitation, microwave-assisted method, and other emerging greener approaches. In view of inherent deficiencies in ZnS QDs namely bandgap alignment and high recombination rate, some modification strategies like doping and heterojunction formation have been explored. Doping is preferred for tuning the band gaps for light absorption upto near-infrared region (NIR) that results in enhanced photocatalytic proficiency. The formation of heterojunction strategies has been put forth owing to the effective charge separation and migration ability. Finally, an outlook regarding unresolved challenges about ZnS QDs photocatalyst is projected for future perspectives in this arena. Graphical abstract: Unlabelled Image Highlights: An account of ZnS QDs as a potential photocatalyst for pollutant degradation. Comprehensive report on the synthesis techniques and effect of reaction conditions. Doping as an effective strategy for ZnS QDs was elaborated. Efficiency enhancements of ZnS QDs through heterojunction formation are discussed. Future scope and existing challenges are deliberated.